Carolina Satyr Hermeuptychia sosybius (Fabricius, 1793) (Insecta: Lepidoptera: Nymphalidae: Satyrinae: Satyrini: Euptychiina) - Denise Tan; Andrea Lucky (EDIS)
This document provides an overview of the Carolina satyr butterfly, Hermeuptychia sosybius. It details the butterfly’s distribution across the southeastern United States, its preferred habitats, and its life cycle stages from egg to adult. The article also highlights the morphological differences between the Carolina satyr and the similar intricate satyr, Hermeuptychia intricata. Additionally, it discusses the butterfly’s feeding habits and the grasses that serve as larval hosts. The document emphasizes the importance of accurate species identification for conservation efforts.